Delta‐Flux: An Eddy Covariance Network for a Climate‐Smart Lower Mississippi Basin. Issue 1 (1st February 2017) - Runkle, Benjamin R. K.; Rigby, James R.; Reba, Michele L.; Anapalli, Saseendran S.; Bhattacharjee, Joydeep; Krauss, Ken W.; Liang, Lu; Locke, Martin A.; Novick, Kimberly A.; Sui, Ruixiu; Suvočarev, Kosana; White, Paul M.
Abstract : Core Ideas: The Lower Mississippi River Basin (LMRB) is agriculturally important and ecologically unique. The Delta‐Flux network will coordinate the activities of 17 eddy covariance towers. The network addresses the need for scaled C and water cycle observations. The network aims to promote sustainable, climate‐smart land management. Delta‐Flux is open to collaborators from strategic sites and relevant disciplines. Networks of remotely monitored research sites are increasingly the tool used to study regional agricultural impacts on carbon and water fluxes. However, key national networks such as the National Ecological Observatory Network and AmeriFlux lack contributions from the Lower Mississippi River Basin (LMRB), a highly productive agricultural area with opportunities for soil carbon sequestration through conservation practices. The authors describe the rationale to create the new Delta‐Flux network, which will coordinate efforts to quantify carbon and water budgets at seventeen eddy covariance flux tower sites in the LMRB. The network structure will facilitate climate‐smart management strategies based on production‐scale and continuous measurements of carbon and water fluxes from the landscape to the atmosphere under different soil and water management conditions. The seventeen instrumented field sites are expected to monitor fluxes within the most characteristic landscapes of the target area: row‐crop fields, pasture, grasslands, forests, and marshes. The network participants are committed to open collaboration and efficient regionalization of site‐level findings to support sustainable agricultural and forestry management and conservation of natural resources.